Involving deprived communities in improving the quality of primary care services: does participatory action research work? - Cawston, Peter G (BioMed Central, 2007)
BACKGROUND: Participation by communities in improving the quality of health services has become a feature of government policy in the United Kingdom. The aim of the study was to involve a deprived community in the UK in shaping quality improvements of local primary care services. The specific objectives were firstly to create participation by local people in evaluating the primary care services available in the area and secondly to bring about change as a result of this process. METHODS: The methods of participatory action research was used. The study was set in an area of high socio-economic deprivation served by a 'Local Health Care Co-operative' in a peripheral housing estate in Glasgow, Scotland. 72 local residents took part in 11 focus groups: eight of these were with community groups and three with other residents. 372 local residents completed questionnaires either by brief face-to-face interviews (114) or by self or carer completion (258). RESULTS: The study group produced recommendations on physical access to the health centre, time constraints in accessing services and problems encountered in individual relationships with health staff. They also highlighted the social gap between health service providers and the daily life of community residents. Action was taken to bring these recommendations to the attention of the Primary Care Organisation. CONCLUSION: Participatory action research was used to involve a deprived community in the UK in a 'bottom-up' approach aimed at improving quality of local primary care services. Although successful in creating a partnership between academic researchers and lay researchers and participation by local people in evaluating the primary care services available in the area, the impact of the study in terms of immediate action taken over specific issues has been modest. The possible reasons for this are discussed.